Find Out Publications for Decade in Local Wisdom: Contribute to Education and Physics Education - Mohd Zaidi Bin Amiruddin; Mohd Zaidi Bin Amiruddin; Binar Kurnia Prahani; Binar Kurnia Prahani; Nadi Suprapto; Nadi Suprapto; Suliyanah Suliyanah; Suliyanah Suliyanah; Achmad Samsudin; Achmad Samsudin (Universitas Lambung Mangkurat, 2023)
The development of local wisdom from various sectors continues to increase yearly, especially in Indonesia. This study aims to find trends, topics, and contributions of local wisdom to the education sector. This research used quantitative research with bibliometrics and assisted with VoSViewer, Word Cloud, MS Excel, and MS Word software to analyze and visualize metadata results obtained from Scopus. The results of this study reveal trends in the development of local wisdom, with the top 100 cited from 2012 to 2021. Then, the topic of local wisdom is dominated by researchers from Indonesia. In addition, the contribution of local wisdom in education continues to grow along with the times, especially in physics education. Furthermore, it is hoped that there will be further research on local wisdom that can be used as a reference source for all things and preserve local wisdom and communities that still need to be held due to changing times. On the other hand, local wisdom can also be known with the slogan “Glocalization”.